Enhancing Mediterranean forage legume production through inoculation with elite rhizobia - Scavo, Aurelio; Maio, Aurora; Calderone, Francesca; La Malfa, Tommaso; Trostle, Calvin; Yates, Ronald J.; Toscano, Stefania; Cavallo, Carmelo; Oteri, Marianna; Furfaro, Maria Elena; Virga, Antonino Nazareno; Scordia, Danilo; et al. (Frontiers in Agronomy, 2025)
Forage legumes play a fundamental role in the sustainability of cropping systems, as rotating species with grain crops, intercrops, or winter cover crops. However, their compatibility with rhizobial inoculants needs context-specific studies. The objectives were to evaluate the effectiveness of three species-specific inoculants [Australian granular (AUG), Australian peat (AUP), and American peat (USP)], compared with a non-inoculated control (CNT). These were applied at the recommended and double dose on five Mediterranean forage legumes (Vicia sativa, Medicago polymorpha, Trifolium michelianum, T. subterraneum, and T. pratense). Plant growth, nodulation, and relative N2 fixation were measured. Species-specific variations were observed for each inoculant. Across the average of legume species, AUG demonstrated the highest growth- and nodulation-promoting effects at both standard and double inoculum doses. The USP was the worst inoculant at the standard dose but induced positive effects at double dose. The relative N2 fixation was only improved at double dose, especially by USP and AUG, whereas only AUP provided significant N2 fixation enhancements at standard dose. Overall, the double dose was the best strategy for all tested forage legumes. These findings suggest that inoculating Mediterranean forage legumes with selected inoculants, especially at double dose, may be an effective solution to increase their N2 fixation ability, reduce the use of mineral N fertilizers, and identify the optimal forage legume × inoculant combinations for intercropping systems with cereals.